ANALISIS PENGEMBANGAN LAHAN: STUDI PADA LAHAN DESA BOMAKI KABUPATEN MALUKU TENGGARA BARAT - SILETTY, PERIANUS J J ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study analyzes the development of fixed asset that is a land owned by the Government of West Southeast Maluku District located at Bomaki Street, South Tanimbar District, West Southeast Maluku. The analysis used in this study is the analysis of land development. This study using the Discounted Cash Flow analysis to determine the market value of the property which was built in this research object. The data used in this study are primary and secondary data. Primary data is from direct observation, the data include the bid price of land in the study and the price of the rental courts. Secondary data were obtained from BPS, BAPPEDA and BPKAD of West Southeast Maluku. Based on market analysis, sport hall is a development that could provide revenue for the government of West Southeast Maluku District with estimated revenue is Rp157.877.461.701,00.